Hubungan Antara Citra Perusahaan dengan Loyalitas Pelanggan Pada PT. Tiki Jalur Nugraha Eka Kurir (JNE) Agen Sayang Jatinangor - Taufiq Hidayat (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2022)
The development of the online shop business today has resulted in competition between companies engaged in the unavoidable shipping service sector, including package delivery service companies. PT. Tiki Nugraha Eka Kurir or JNE has a good image in the the public and has loyal customers as evidenced by receiving the prestigious award, the Indonesia Top Digital Public Relations Award 2022 for the third time since 2020. This study aims to analyze how customers evaluate the company's image. formed, how loyal they are to the company, and how big is the relationship between company image and customer loyalty. The research method used is a survey, and the sampling technique is probability or random. The sampling method was simple random sampling in a systematic or ordinal way, while the techniques in data collection were library research, field studies and questionnaires distributed to 25 respondents. For data analysis techniques using MSI, and hypothesis testing were carried out by t-test. From the results of the study it was found that the image formed was good but could still be further optimized. For a relatively moderate level of customer loyalty, in other words, customers still have the opportunity to switch to competing companies so that the company should be able to implement a better strategy to strengthen a sense of loyalty from its customers. The calculation results obtained a total effect of 46.10% and significant, the remaining 53.90% influenced by other variables that were not researched.